ChemInform Abstract: One‐Pot Two‐Step Synthesis of 1‐(Ethoxycarbonyl)indolizines via Pyridinium Ylides. Issue 11 (18th March 2014) - Allgaeuer, Dominik S.; Mayr, Herbert
Abstract The reaction of readily prepared pyridinium and isoquinolinium ylides with arylidene‐malonates is investigated.